The History of Natural Stone in Saint-Petersburg - Panova, Elena (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
The book introduces readers to the heritage of St. Petersburg, sharing the geological history of a unique city, a world heritage site, and part of the UNESCO list. It also explains the role of small towns and fortresses near St. Petersburg, whose stone decoration played an essential role in the city's evolution and was key in the history of neighboring cultures. The book also describes the main architectural symbols of St. Petersburg, such as the Alexander Column, the Bronze Horseman, the Peter and Paul Fortress and more. In addition to five guided tours of the city center, it offers descriptions of historic quarries, some of which are now open-air museums.
Saint Petersburg - the city of stone -- Saint Petersburg - the stones city -- The Bronze Horseman and Thunder Stone - the symbol of St. Petersburg -- Peter and Paul Cathedral - the beginning of St. Petersburg -- Alexander Column - the world's largest monolith -- Natural stone in the modern St. Petersburg -- Part II. Historical quarries of natural stone -- History of stone quarrying in Virolahti area -- Serdobolsky granites from Lake Ladoga -- Granite necklace of the Karelian Isthmus -- Ruskeala marble - joyful stone of Karelia -- Part III. Natural stone in the history of two cultures -- Saimaa Canal - the history of the sea route -- Stones of Valaam and Novovalaam monasteries -- Natural Stone in church buildings -- Towns-fortresses (Vyborg, Korela) -- Dragon's Teeth - Mannerheim defense lines -- Life and Stone (bridges, roads, dwellings, basements). .
Keywords: Earth sciences; Biogeography; Architecture; Geochemistry; Geotechnical engineering; Earth Sciences; Biogeosciences; Architecture; Geochemistry; Geotechnical Engineering and Applied Earth Sciences